A motivation model of sex addiction – Relevance to the controversy over the concept. (November 2022) - Toates, Frederick
Abstract: An integrative model of sexual addiction is presented, involving a combination of models based upon (i) incentive motivation theory and (ii) the dual organisation of the control of behavior. The model is related to ongoing arguments about the validity of the notion of addiction when applied to sexual behavior. It is suggested that the evidence strongly favors the viability of an addiction model of sex. Strong similarities to the classical addiction to hard drugs are observed and features can be better understood with the help of the model. These include tolerance, escalation and withdrawal symptoms. It is argued that other candidates for accounting for the phenomena, such as obsessive-compulsive behavior, faulty impulse control, high drive and hypersexuality do not fit the evidence. The role of dopamine is central to the model. The model's relevance to stress, abuse, development, psychopathy, fantasy, sex differences, evolutionary psychology and the interaction with drug-taking is shown. Highlights: A combination of (i) an incentive motivation model of sex and (ii) dual control theory is presented. By the criteria of (i) suffering and (ii) a shift in weight of control from goal-based to stimulus-based, sex can become addictive. Scrutiny of the criticisms of the notion of sex as addiction reveals them to be invalid. Similarities between sex addiction and drug addiction are noted. Out-of-control sexual behavior is not best characterized as hypersexuality, high drive or an impulse control disorder.